SISTEM INFORMASI PRODUK UNGGULAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN KETAPANG BERBASIS WEB - Novi Indah Pradasari; Eka Wahyudi; Darmanto Darmanto (STEKOM PRESS, 2021)
At the present time of the pandemic, it is difficult for the world's most unusual cuttlefish to market its products. Thus, umkm needs to be provided with facilities to market the products online. Special-based backends are one of the media for selling by-products on the catapult. The purpose of this research is to construct typical web-based appendage by-by-products. The purpose of this research is to construct typical web-based appendage by-by-products. Research methods used in the construction of systems on this research are the methods of research and development (R & D). This study provides several design systems, the design of system architecture, the DFD system, the design of the interface, and the design of system testing. The system was created using the framework laravel. As for the results of the final assignment research